Answer:
![y <x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zzzgiqgplrq940wo1rcyp20o4zozqj0lff.png)
![y>x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g769s080nhwfhhzhs35tihotkksp8md7at.png)
Explanation:
According to the graph, the system is formed by two inequalities. Let's find out the equation to each line in first place.
Notice that the upper line passes through points (-1,0) and (0,1). First, we find its slope
![m=(y_(2)-y_(1) )/(x_(2)-x_(1) )=(1-0)/(0-(-1))=(1)/(1)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v9ykixdobf3gqz9g4umqawsehcl4zjam90.png)
Then, we use the point-slope formula to find the equation
![y-y_(1) =m(x-x_(1) )\\y-0=1(x-(-1)\\y=x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vsojaavwb7dxc74e2tv55g3ljgxyew5r6w.png)
Now, the dashed line indiactes that the inequalities must have sings < or >.
Notice that point (0,0) is part of its solution, that means the inequality is
![y <x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zzzgiqgplrq940wo1rcyp20o4zozqj0lff.png)
We do the same process to find the other inequality.
The line passes through points (0,-2) and (2,0).
![m=(y_(2)-y_(1) )/(x_(2)-x_(1) )=(0-(-2))/(2-0)=(2)/(2)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dd9a0q0s2z1lmrsz2zguuez6ii5p2w0nsl.png)
Then,
![y-y_(1) =m(x-x_(1) )\\y-0=1(x-2)\\y=x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jtpcz1zithlguxuc9dskrxdu1trwi4qr82.png)
Notice that point (0,0) is part of its solution, so the inequality is
![y>x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g769s080nhwfhhzhs35tihotkksp8md7at.png)
Therefore, the system of inequalities is
![y <x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zzzgiqgplrq940wo1rcyp20o4zozqj0lff.png)
![y>x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g769s080nhwfhhzhs35tihotkksp8md7at.png)